Discrimination against women in Malaysia / Intan Zarith Soraya Shahfawi...[et.al] - Shahfawi, Intan Zarith Soraya; Rashidi, Muhammad Nur Aiman; Md Khairi, Muhammad Mifdhal Muiz; Mohd Razali, Nuraliafitri; Shamsul Amir, Shahira Amiera (Faculty of Communication & Media Studies, 2019)
Feminism is a social movement of an organized group that acts consciously to promote or resist change through collective action. Feminism movement in Malaysia as in other developing countries and in the West has the same goal for universal women, whether equality in economics, education, politics, or social. This study was done in order to find the level of discrimination of women in Malaysia. This study involved 487 respondents and the respondents were gained from an online survey through Google Survey Form. The form has been distributed on social medias and from that platform we gained all that respondents and used that as data collection. At the end, we now know that there are not much discrimination against women in Malaysia with low mean of 1.49